Mapping of the gene for cleidocranial dysplasia in the historical Cape Town (Arnold) kindred and evidence for locus homogeneity. Issue 6 (June 1996) - Ramesar, R S; Greenberg, J; Martin, R; Goliath, R; Bardien, S; Mundlos, S; Beighton, P
Abstract : Cleidocranial dysplasia (CCD) is an autosomal dominant disorder, features of which include a patient anterior fontanelle, a bulging calvarium, hypoplasia or aplasia of the clavicles, a wide public symphysis, dental anomalies, vertebral malformation, and short stature. The Cape Town kindred which is under our genetic management was originally described more than four decades ago and now consists of more than 1000 people. Following reports of rearrangements on chromosomes 6 and 8 in people with CCD, we have carried out linkage analyses between highly information microsatellite dinucleotide repeat markers in the rearranged regions and the disorder in a branch of this South African CCD kindred, consisting of 38 subjects, 18 of whom are affected. Maximum lod scores (at theta = 0.00) of 7.14 (for marker D6S459), 4.32 (TCTE), 4.99 (D6S452), 5.97 (D6S269), and 3.95 (D6S465) confirm linkage of the disorder to the short arm of chromosome 6. Our data indicate that the CCD gene is located within a minimal region of approximately 10 cM flanked by the marker D6S451 distally and D6S466 proximally. This information is vital towards isolating and characterising the gene for CCD, and is being used to construct a physical map of 6p21.1-6p21.3. More importantly, mapping of the locus in the South African kindred of mixed ancestry, in which the "founder" of the disorder was of Chinese origin, suggests that a single locus is responsible for classic CCD.